Bank Profitability Level Based on Good Corporate Governance, Macroeconomics, and Specific Banks in Foreign Exchange Banks in Indonesia - Hasddin Hasddin; Muhammad Sardy Sujadi Mido; Melati Melati; Misnawati Misnawati; Muhammad Irfan Rama; Andi Muh Dzul Fadli; Nartin Nartin; Mirad Mirad; Marjani Marjani; Dahlifah Dahlifah; Rimi Gusliana Mais (Center for Risk Management & Sustainability and RSF Press, 2026)
This study examines how Good Corporate Governance (GCG), macroeconomic conditions, and bank-specific characteristics influence the profitability of foreign exchange banks in Indonesia. Using a quantitative approach, the research analyzes secondary data from the annual financial statements of foreign exchange banks listed on the Indonesia Stock Exchange over the period 2014–2022. The study investigates the direct effects of GCG on profitability, the influence of macroeconomic factors on bank-specific characteristics and profitability, and the role of bank-specific characteristics in determining profitability. Data were analyzed using partial least squares with a resampling technique to test the significance of relationships. The results show that GCG contributes positively to overall bank financial performance; however, its direct effect on profitability is positive but not statistically significant. Macroeconomic conditions are found to positively affect bank-specific characteristics, while exerting a negative influence on profitability. In contrast, bank-specific characteristics—particularly bank size, total assets, and deposit growth—have a significant and positive impact on profitability. These findings suggest that strengthening governance practices alone is not sufficient to directly increase profitability. Banks also need to improve asset management and expand deposit bases to enhance financial performance. In addition, effective management of macroeconomic risks is essential to reduce their adverse effects on bank profitability. This study provides empirical insights into the interaction between governance, economic conditions, and internal bank factors in Indonesia’s banking sector.